Combining with immunotherapy is an emerging trend for local treatment of colorectal cancer liver metastases: a bibliometric analysis - Shao, Bin; Yin, Ya-Shi; Wei, Yi-Nuo; Dong, Peng; Ning, Hou-Fa; Wang, Guang-Zhi (Frontiers in Oncology, 2025)
BackgroundA growing body of evidence has demonstrated the expanding role of local treatment in managing colorectal cancer liver metastases (CRCLM). To identify current research trends and forecast future directions, we conducted a bibliometric analysis to examine global collaboration patterns and academic influence across countries, institutions, journals, and authors.Materials and methodsRelevant articles and reviews on CRCLM local therapies were systematically retrieved from the Web of Science Core Collection. The bibliometric package in R software and VOSviewer software were used to analyze countries, institutions, journals, authors, and keywords. The research status and key areas of local treatment of colorectal cancer liver metastases were analyzed by keywords.ResultsThe analysis encompassed 2,695 articles published between 2008 and 2023. The United States emerged as the leading contributor, with Memorial Sloan Kettering Cancer Center producing the highest number of publications (n=178). Among journals, Annals of Surgical Oncology ranked first in publication volume, while Journal of Vascular and Interventional Radiology achieved the highest citation count. The local treatment modalities for CRCLM included transarterial therapies (radioembolization and chemoembolization), hepatic artery infusion chemotherapy and immunotherapy, imaging guidance methods, hepatectomy and survival, and ablation and stereotactic body radiotherapy. Recent studies highlighted ablations, microspheres, and immunotherapy as key research areas, with thematic mapping identifying immunotherapy as an emerging niche field.ConclusionCRCLM local treatment research focuses on integrating local and systemic therapies. Preclinical studies, RFA with anti - PD - 1 agents, show enhanced anti - tumor immunity and survival. While the synergy of local and immunotherapy is confirmed, large - scale clinical evidence is still needed. Thus, cross - disciplinary cooperation is urgently required to boost translational medical research.